DECISION SUPPORT SYSTEM FOR SERVICE QUALITY ASSESSMENT AT SUSHI XYZ RESTAURANT USING THE FUZZY MAMDANI METHOD - Nadya, Nadya; Karimah, Aisya Cahya; Saragih, Abil Ghozali; Nainggolan, Arilius Kasdar (PT Siantar Codes Academy Publisher, 2025)
Service quality assessment is essential for maintaining the competitiveness of Sushi XYZ restaurant. However, manual evaluations often face challenges such as subjectivity and inconsistency. This study implements the Fuzzy Mamdani method to develop a Decision Support System (DSS) that provides objective and measurable evaluations based on three main criteria: Service Speed, Friendliness, and Cleanliness. The process begins with fuzzification to convert numerical data into fuzzy categories, followed by rule-based inference using IF-THEN logic, and concludes with defuzzification using the centroid method to produce a crisp output value. The results show that Respondents A and E fall into the